Pengembangan Media Pembelajaran Berbasis Whiteboard Animation dalam Pembelajaran Biologi Kelas XI pada Materi Sistem Pencernaan Makanan - Ardian, Nini; Hutasuhut, Melfa Aisyah; Rohani, Rohani (Bioscientist : Jurnal Ilmiah Biologi, 2022)
The process of biology study by using the whiteboard animation medium will allow the teacher to use it as a fascinating, creative introduction to study. The study aim is to develop a whiteboard animation learning medium, describing the worthiness of a whiteboard animation based learning media. The method used in the study is the method of research and development (r&d). The subject of this study is the sophomores, Sibolga high school. The data-collection techniques used in this study are observation, angket, and interview. The analysis technique used is quantitative descretive. Studies show that development of whiteboard animation based media studies meets the requirements of a highly deserved validation of experts with a 92.4% percentage in the category. Student responses get an 80,21% interesting category, which will make whiteboard animation worthy of use in biology study.